Aerobic Versus Resistance Training Effects on Ventricular-Arterial Coupling and Vascular Function in the STRRIDE-AT/RT Trial - Lekavich, Carolyn L.; Allen, Jason D.; Bensimhon, Daniel R.; Bateman, Lori A.; Slentz, Cris A.; Samsa, Gregory P.; Kenjale, Aarti A.; Duscha, Brian D.; Douglas, Pamela S.; Kraus, William E. (Frontiers in Cardiovascular Medicine, 2021)
Background: The goal was studying the differential effects of aerobic training (AT) vs. resistance training (RT) on cardiac and peripheral arterial capacity on cardiopulmonary (CP) and peripheral vascular (PV) function in sedentary and obese adults. Methods: In a prospective randomized controlled trial, we studied the effects of 6 months of AT vs. RT in 21 subjects. Testing included cardiac and vascular ultrasoundography and serial CP for ventricular-arterial coupling (Ees/Ea), strain-based variables, brachial artery flow-mediated dilation (BAFMD), and peak VO2 (pVO2; mL/kg/min) and peak O2-pulse (O2p; mL/beat). Results: Within the AT group (n = 11), there were significant increases in rVO2 of 4.2 mL/kg/min (SD 0.93) (p = 0.001); O2p of 1.9 mL/beat (SD 1.3) (p = 0.008) and the brachial artery post-hyperemia peak diameter 0.18 mm (SD 0.08) (p = 0.05). Within the RT group (n = 10) there was a significant increase in left ventricular end diastolic volume 7.0 mL (SD 9.8; p = 0.05) and percent flow-mediated dilation (1.8%) (SD 0.47) (p = 0.004). Comparing the AT and RT groups, post exercise, rVO2 2.97, (SD 1.22), (p = 0.03), O2p 0.01 (SD 1.3), (p = 0.01), peak hyperemic blood flow volume (1.77 mL) (SD 140.69) (p = 0.009), were higher in AT, but LVEDP 115 mL (SD 7.0) (p = 0.05) and Ees/Ea 0.68 mmHg/ml (SD 0.60) p = 0.03 were higher in RT. Discussion: The differential effects of AT and RT in this hypothesis generating study have important implications for exercise modality and clinical endpoints.